2022
DOI: 10.1073/pnas.2118425119
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian nonparametric inference for heterogeneously mixing infectious disease models

Abstract: Significance Mathematical models of infectious disease transmission continue to play a vital role in understanding, mitigating, and preventing outbreaks. The vast majority of epidemic models in the literature are parametric, meaning that they contain inherent assumptions about how transmission occurs in a population. However, such assumptions can be lacking in appropriate biological or epidemiological justification and in consequence lead to erroneous scientific conclusions and misleading predictions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…It is worth noting that FMD pathogenesis and transmission dynamics are different between species, including viral replication, persistence, incubation period, and potential to infect the same and/or different hosts with different transmission probabilities (Alexandersen et al, 2003; Arzt et al, 2011; Moreno-Torres et al, 2022; Stenfeldt et al, 2016), for example, pigs emit more viruses than cattle and sheep which increases the transmission rate when the pigs are the more infectious host when compared with other domestic species (Brown et al, 2022; Donaldson and Alexandersen, 2002; Moreno-Torres et al, 2022). Thus, it is pivotal that such heterogeneity in the transmission dynamics is considered while modeling either within or between-farm transmission dissemination (Seymour et al, 2022). Whilst, between farm transmission, primarily occurs through the direct contact among susceptible and infected animals (Alexandersen et al, 2003; van Andel et al, 2021), field observation and experimental trials demonstrated the spread of the virus via indirect contact with fomites and long-distance transport of aerosols, a process known as spatial transmission (Chakraborty et al, 2021; Guyver-Fletcher et al, 2021; Sellman et al, 2020; van Andel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is worth noting that FMD pathogenesis and transmission dynamics are different between species, including viral replication, persistence, incubation period, and potential to infect the same and/or different hosts with different transmission probabilities (Alexandersen et al, 2003; Arzt et al, 2011; Moreno-Torres et al, 2022; Stenfeldt et al, 2016), for example, pigs emit more viruses than cattle and sheep which increases the transmission rate when the pigs are the more infectious host when compared with other domestic species (Brown et al, 2022; Donaldson and Alexandersen, 2002; Moreno-Torres et al, 2022). Thus, it is pivotal that such heterogeneity in the transmission dynamics is considered while modeling either within or between-farm transmission dissemination (Seymour et al, 2022). Whilst, between farm transmission, primarily occurs through the direct contact among susceptible and infected animals (Alexandersen et al, 2003; van Andel et al, 2021), field observation and experimental trials demonstrated the spread of the virus via indirect contact with fomites and long-distance transport of aerosols, a process known as spatial transmission (Chakraborty et al, 2021; Guyver-Fletcher et al, 2021; Sellman et al, 2020; van Andel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The most common simplification is to restrict the epidemiological models to a single species (Chanchaidechachai et al, 2021; Sseguya et al, 2022). Despite the different applications and efforts in modeling FMD, questions on measuring the epidemic trajectory and epidemic control strategies while considering heterogeneous transmission dynamics among the different susceptible species coexisting on the same farms remain outstanding (Seymour et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations